Teorias efetivas e violação de sabor leptônico em decaimentos do Higgs - Prado, Leônidas Augusto Fernandes do [UNESP] (2015)
We consider the Higgs Lepton Flavor Violating decay h→ 'tau' 'mü' in the framework of eﬀective theories, on which CMS reported a 2.5 σ excess of events. The operator that is responsible for this process, however, is in many models correlated to dipole operators that are already under stringent experimental constraints. We then explore in which cases it is possible to obtain a ﬂavor violating operator that is big enough to be seen in Higgs decays at the LHC, while still respecting the leptonic radiative decay bounds. We also present two models, a simpliﬁed Composite Higgs model and a Higgs Portal model, showing how the process h→ 'tau' 'mü' is generated in each of them. We ﬁnd that if the CMS signal is conﬁrmed, the second model is favored, while it is unlikely that the ﬁrst model will be able to explain it